Novel N-Benzoylimidazolium Ionic Liquids Derived from Benzoic and Hydroxybenzoic Acids as Therapeutic Alternative Against Biofilm-Forming Bacteria in Skin and Soft-Tissue Infections - Echeverria-Morgado, J (Academic Press, 2022)
The skin and soft tissue infections (SSTIs) -producing pathogens have acquired resistance to a wide range of antimicrobials, thus it is highly relevant to have new treatment alternatives. In this study, we report the synthesis, characterization, and antibacterial activity of three novel series of ionic liquids (ILs) derived from benzoic and hydroxybenzoic acids, with different lengths of the alkyl chain. The minimum inhibitory concentration (MIC) were tested in Gram-positive: Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus pyogenes, and Gram-negative: Acinetobacter baumannii and Escherichia coli, showing a MIC range of 0.01562–2.0 mM, with the activity varying according to the aromatic ring functionalization and the length of the alkyl chains. Regarding the antibiofilm activity, different efficacy was observed among the different ILs, some of them presenting antibiofilm activities close to 80% as in the case of those derived from syringic acid with an alkyl chain of six carbon atoms against Pseudomonas aeruginosa. Furthermore, the cell viability in HaCaT cells was determined, showing a half maximal effective concentration (EC50) values higher than the MIC values. The antimicrobial and antibiofilm results, along with not producing cellular toxicity at the MIC values shows that these ILs could be a promising alternative against SSTIs. © 2022 Elsevier Inc.